Análise das características dimensionais e resistência à fadiga de instrumentos rotatórios de NiTi Twisted File e RaCe - Rafael Rodrigues Soares de Magalhaes (2010)
This work was a study of structural characteristics, physical and mechanical properties of NiTi endodontic instruments Twisted File 25/.06 and .08, RaCe 25/.04 and .06. The geometric and dimensional characteristics of the instruments were analyzed and measured by the software ImagePro Plus 6.0 (Media Cybernetics, Silver Spring, MD, USA). The topographic features were evaluated by scanning electron microscopy (SEM), chemical composition was analyzed semi-quantitatively by proton energy X-ray (EDS), the crystalline structure of the alloy identified by X-ray diffraction (XRD) while the transformation temperatures were determined by differential scanning calorimetry (DSC). Fatigue strength was evaluated in a bench device using an artificial canal with a radius of curvature of 5mm and 45° angle. RaCe instruments were standardized geometric and surface characteristics consistent with those described by the manufacturer (FKG, La Chaux-de-Fonds, Switzerland). Already instruments Twisted File not presented the geometric characteristics and surface suggested by the manufacturer (SybronEndo, Orange, CA). The instruments of the two systems were in satisfactory stoichiometric and transformation temperatures favor the occurrence of superelasticity. Although the manufacturer Twisted File System report that their instruments are composed of R-Phase, the presence of this phase was not detected in tests carried out. The diffraction patterns obtained with instruments and Twisted File RaCe demonstrated the presence of peaks of higher intensity of -Phase. In fatigue tests, the resistance of the instruments decreased with increasing size. The results obtained and analyzed by ANOVA, with a coefficient of reliability of 95%, indicated that the TF 25/.06 instruments showed a fatigue life 16,0% higher when compared to RaCe 25/.04 instruments and tools TF 25/.08 fatigue life showed a 18,0% increase compared to RaCe 25./06 instruments.